2011
DOI: 10.1097/aog.0b013e3182167627
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stillbirth in Zambia

Abstract: Stillbirth is a major contributor to poor perinatal outcomes in Lusaka. Many deaths appear avoidable through investment in antenatal screening and better labor monitoring. Stillbirth should be adopted as a routine health indicator by the World Health Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
53
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 17 publications
13
53
3
Order By: Relevance
“…However, a prior publication found that women with delivery information in ZEPRS did not differ in any clinically significant way from women without delivery information. 36 Second, we do not have complete information available about laboratory malaria diagnosis, CTX prophylaxis, socioeconomic status, or HIV RNA viral load and were unable to adequately examine or control for these factors. Third, there are women in our study with more doses of SP than ANC visits.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prior publication found that women with delivery information in ZEPRS did not differ in any clinically significant way from women without delivery information. 36 Second, we do not have complete information available about laboratory malaria diagnosis, CTX prophylaxis, socioeconomic status, or HIV RNA viral load and were unable to adequately examine or control for these factors. Third, there are women in our study with more doses of SP than ANC visits.…”
Section: Discussionmentioning
confidence: 99%
“…This finding reinforces the need of training of midwives in identification and proper referral of breech cases to proper facilities. Studies 23,24 have shown patients without antenatal care had two fold increased perinatal morbidity. Emergency caesarean sections were performed in 54 (35%) of patients selected for vaginal deliveries reasons being dysfunctional labour, fetal distress, footling breech & cord prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that babies who die before the onset of labor, or ante partum stillbirths, account for two-thirds of all stillbirths in countries where the mortality rate is greater than 22 per 1,000 births [7]. From previous studies, preterm birth, increasing maternal age, history of stillbirth, reported hypertension, extremes of neonatal birth weight, cesarean delivery, operative vaginal delivery, and assisted breech delivery were all significantly associated with still birth [8]. According to Ethiopian Demographic and Health Survey in 2011, In Ethiopia, high rate of neonatal mortality (37 deaths per 1,000 live births)is reported and preterm birth is believe to be a major and direct cause of neonatal mortality [9].…”
Section: Introductionmentioning
confidence: 99%